Teacher Professional Identity and Perfomer Identity: Where Does the Stage Cease and the Class Begin? - Ambrazevičiūtė, Birutė (Acta Paedagogica Vilnensia, 2020)
The focus of the article is on the process of becoming a teacher. Many researchers have concluded that this process is of profound, complex, ever-evolving nature, during which teachers attempt to define their role and their entity. Identity itself brings out another problem of identification with the subject. Thus, more and more studies have been exploring professional teacher identities in different fields regarding the interaction between subject and teacher identities. The aspects of professional identity development among teachers of stage performers from the specific field of artistic education have been chosen for the research due to the lack of scientific research worldwide so far. The arts school case study of professional identity among teachers of stage performers from the development point of view has showed that the professional identity development of teachers among stage performers of an arts school is of a wide scope and possesses its own features. In the course of first socialization, the performer identity is perceived, while the teacher role is selected during the second socialization. No identity conflict has been observed between performer and teacher identities, they help maintain the mission of an artist. Everyday pedagogical practice, knowledge and skills by means of reflection and conversation contribute the understanding of what a teacher role is. Creativity and openness are essential for interaction with the milieu.
Keywords: teacher; performer; professional identity; process of becoming a teacher